2020
DOI: 10.1371/journal.pone.0239952
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 deficiency predisposes to spontaneous otitis media

Abstract: Signal transducer and activator of transcription 1 (STAT1) is known to be an important player in inflammatory responses. STAT1 as a transcription factor regulates the expression of multiple proinflammatory genes. Inflammatory response is one of the common effects of ototoxicity. Our group reported that hair cells of STAT1 knockout (STAT1-KO) mice are less sensitive to ototoxic agents in-vitro. The effect of inflammatory responses in STAT1-KO mice has primarily been studied challenging them with several pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our histopathology studies showed significant damage to the neural and vascular structures in the cochlea of the LASV infected mice. There is a clear difference to the reported spontaneous middle ear infection in Stat1-KO mice with no apparent pathology in the cochlea [ 23 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our histopathology studies showed significant damage to the neural and vascular structures in the cochlea of the LASV infected mice. There is a clear difference to the reported spontaneous middle ear infection in Stat1-KO mice with no apparent pathology in the cochlea [ 23 ].…”
Section: Discussionmentioning
confidence: 84%
“…The Stat1-KO mice are known to develop middle ear infection spontaneously around 12–13 weeks of age resulting in unilateral or bilateral conductive hearing loss, which resolves in several weeks [ 23 ]. At the onset of hearing loss at 3 w.p.i., our Stat1-KO mice were around the susceptible age for developing middle ear infections.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-a), various kinds of interleukin and other immune factors have been studied. 15 , 16 Additionally, CD4+ T cells and CD8+ T cells have been investigated as immune cell markers in OME. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-a), various kinds of interleukin and other immune factors have been studied. 15,16 Additionally, CD4+ T cells and CD8+ T cells have been investigated as immune cell markers in OME. 17 These various lines of research contribute to our understanding of the multifactorial nature of OME, involving factors such as bacterial infection, inflammatory responses, radiotherapy-related changes, and allergic processes.…”
Section: The Clinical Etiology Of Otitis Media With Effusionmentioning
confidence: 99%
“…Under normal physiological conditions, the STAT protein exists in the cytoplasm in an inactive form or is briefly activated (Bodmer et al, 2020). A variety of cytokines attach to type I/II cytokine receptors to dimerize the receptors.…”
Section: Activation and Inhibition Of The Jak-stat Pathwaymentioning
confidence: 99%